Police data searching and data usage in criminal profiling (Academic Journal of Internal Affairs, 2022)
In the present study, I present the scope of data to be obtained in police proceedings, as well as the rules and legal framework of data collection. Forensic data are of key importance for profiling, as the reliability of this method depends, among other things, on the quality of the data obtained. Thus, knowledge of the legal framework and follow-up of forensic recommendations is necessary for all investigators and all analytical units dealing with profiling. In addition, I present the past and present of domestic profiling, as well as mention future development directions.
Keywords: data searching; data usage; criminalistics; criminal profiling